Static Magnetic Monopoles Configurations. - Teh, Rosy; Wong, Khai Ming (2005)
Recently, we have reported on the existence of some monopoles, multimonopole, and antimonopoles configurations. In this paper we would like to give a brief !eview of the• •different exact monopoles, multimonopole, antimonopoles and vortex•rings configurations of the magnetic ansatz of Ref. [9]